Common Variation in EDN1 Regulatory Regions Highlights the Role of PPARγ as a Key Regulator of Endothelin in vitro - Lago-Docampo, Mauro; Solarat, Carlos; Méndez-Martínez, Luis; Baloira, Adolfo; Valverde, Diana (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary Arterial Hypertension (PAH) is a rare disease caused by the obliteration of the pulmonary arterioles, increasing pulmonary vascular resistance and eventually causing right heart failure. Endothelin-1 is a vasoconstrictor peptide whose levels are indicators of disease progression and its pathway is one of the commonest targeted by current treatments. We sequenced the EDN1 untranslated regions of a small subset of PAH patients, predicted the effect in silico, and used a luciferase assay with the different genotypes to analyze its influence on gene expression. Finally, we used siRNAs against the major transcription factors predicted for these regions (PPARγ, KLF4, and VDR) to assess Endothelin-1 expression in cell culture and validate the binding sites. First, we detected a SNP in the 5’UTR (rs397751713) and another in the 3’regulatory region (rs2859338) that increased luciferase activity in vitro depending on their genotype. We determined in silico that KLF4/PPARγ could be binding in the rs397751713 and VDR in rs2859338. By using siRNAs and luciferase, we determined that PPARγ binds differentially in rs397751713. PPARγ and VDR Knock-Down, increased EDN1 mRNA levels and Endothelin-1 production in PAECs, while PPARγ and KLF4 Knock-Down increased the Endothelin-1 production in HeLa. In conclusion, common variants in EDN1 regulatory regions could alter Endothelin-1 levels. We were able to validate that PPARγ binds in rs397751713 and is key to regulate Endothelin-1. Also, KLF4 and VDR regulate Endothelin-1 production in a cell-dependent manner, but for VDR this interaction does not happen by binding directly to the regions we studied.